STOMATOPOD CRUSTACEA COLLECTED BY THE MISSION CORINDON II IN THE MAKASSAR STRAIT, INDONESIA - Moosa, Mohammad Kasim; Cleva, Regis (Marine Research in Indonesia, 1984)
Seventeen species of Stomatopoda belonging to five families have been collected in the Strait of Makassar, Indonesia during the Franco-Indonesian mission "CORINDON II". Four species of the family Squillidae: Kempina mikado, Lenisquilla spinosa, Oratosquilla imperialis, and O. ornata are for the first time reported to exist in the Indonesian waters.